From Likes to Bonds: A Scoping Review on the Impact of Social Media on Youth Social Interaction Patterns - Sitinjak, Charli; Kristiyani, Veronica; Handoko, Daniel (Nusantara Journal of Behavioral and Social Science, 2025)
Social media has profoundly reshaped the way youth interact, communicate, and build relationships in the digital age. As platforms like Instagram, TikTok, Facebook, and WhatsApp become central to daily life, understanding their psychosocial impacts on young people is critical. This scoping review aims to map and synthesize existing research on how social media influences youth social interaction patterns. A total of 82 studies published between 2020 and 2025 were analyzed, covering diverse cultural and geographical contexts. Thematic analysis identified four key areas: (1) social media as a catalyst for friendship formation, (2) evolving communication styles shaped by visual and ephemeral content, (3) the rise of digital intimacy and emotional support networks, and (4) the amplification of peer conflict, social comparison, and algorithmic pressures. The findings reveal both opportunities (e.g., global connections and creative self-expression) and risks (e.g., performative self-presentation, cyberbullying, and FOMO). Practical recommendations include implementing digital literacy programs in education, fostering authentic connections through platform design, and developing policies for algorithmic transparency and youth online safety. This review highlights the need for intersectional and globally aware frameworks and calls for longitudinal research to inform interventions that promote youth well-being in digital spaces.